Pendampingan Seni Batik Bersama Komunitas Shibori Tingkat Pemula - Intan Kusuma Wardani; Siti Rabiatul Adawiyah; Muhammad Sarifuddin; Nofisulastri (Puslitbang Sekawan Institute Nusa Tenggara, 2021)
This community service activity is expected that students will be able to independently transfer soft skills to empower the community through KKN (Real Work Lectures) and the impact of independent campus activities will give students the ability to compete in the world of work and even open new job opportunities. One of the solutions offered in this community service activity is the provision of soft skills with the vision of preserving the art culture of batik, namely batik shibori or tye dye. Achievement of community service activities involving Undikma students as agents of change is the hope of helping social change in the community as psychological health first aid for disaster survivors, especially the Covid 19 pandemic. The implementation method consists of five stages, namely communication; observation and legalization, strategies; execution (socialization of activities and training of Shibori batik), and evaluation. The activity was carried out from 03 September 2020 to 02 June 2021 with the target being Undikma students as members of the NTB shibori community. Each target has succeeded in making Shibori batik techniques with folding and coloring techniques based on their own creations with satisfactory category achievements. Where’s ≥ 90% of the participants (targets) were able to follow and demonstrate basic shibori techniques in folding and tying fabrics which are shown in independent demonstrations (without discussing or asking questions) and able to make decisions independently at the selection stage and how to dye the fabric colors which will later be used the final product.